MAIN DIRECTIONS OF ECOLOGICAL MANAGEMENT AND AUDIT OF THE COMPANY AS FACTOR OF PREVENTION OF THE GLOBAL DISASTER - Eleonora Navasardova; Oksana Takhumova (Вестник Северо-Кавказского федерального университета, 2022)
During an era of globalization and intensive development of the market relations in the world the increasing value is found by the problems affecting aspects of impact on the environment. With respect thereto the characteristic of development and application of various methods ofprevention of an environmental disaster is provided in work. Relevance of carrying out environmental audit and development of concepts of ecological management within various companies participating in the world economic relations that has economic, ecological and social aspects is reasoned. Importance of carrying out environmental audit for ensuring normal functioning of the companies and their active interaction with all market structures in world practice is shown.